Active Sulpho-belite cements. Hydration mechanisms and mechanical properties - Álvarez-Pinazo, Gema (Servicio de Publicaciones y Divulgación Científica, 2015)
The threat of climate change is considered one of the major environmental challenges for our society, where carbon dioxide (CO2) is one of the main Greenhouse gases (GHGs). Every ton of ordinary Portland cement (OPC) produces about one ton of CO2. The design of new formulations of cements is advisable to provide a solution. One alternative consists on Belite Calcium Sulpho-Aluminate (BCSA) cement, that can release ~0.22 tons of CO2/ton of clinker less than OPC. The most common formulation of BCSA clinkers consists on beta-C2S, orthorrombic-C4A3S and C4AF. Due to the presence of the latter, these cements are usually called iron-rich-BCSA (BCSAF). These cements are less limestone demanding and need less clinkering temperature, but compromise the early-age strength development because beta-C2S reacts slowly. This problem may be overcome by the activation of belite and the presence of high amounts of C4A3S. Although BCSAF are promising alternatives, before implementation in Europe, all the steps evolved in the process need to be under control [clinkering (activation/composition; temperature), hydration (rheological behaviour; phase assemblage), and final performances (mechanical strength; dimensional stability)]. This Thesis is focused on the study and optimisation of those parameters to improve the final performances of BCSAF mortars. One of the main objectives was to perform the "medium-scale" synthesis (2kg) of two BCSAF clinkers in our laboratory (50wt% C2S, 30wt% C4A3S, 20wt% C4AF). One of the clinkers was “activated” by adding borax. The aim of the activation has been obtaining clinkers with different belite (-C2S/'H-C2S) and ye'elimite (orthorhombic/pseudo-cubic) polymorphs to understand the effect of the polymorphism on the paste hydration mechanism and mechanical performances of the mortars. X-ray diffraction coupled with Rietveld analysis is a suitable methodology to obtain quantitative phase analysis of these materials including the amorphous/sub-cooled and/or non-crystalline phases. The quantification of the amorphous content is performed using two approaches: i) external standard procedure (G-factor method) with reflection geometry; and ii) internal standard procedure (ZnO) with transmission geometry. Other objective of this Thesis was to understand the influence of calcium sulphate source (type and amount) on the hydration of BCSAF-cements. BCSAF clinkers were mixed with different types and amounts of calcium sulphate sources (gypsum, anhydrite, bassanite) and prepared at a w/c=0.55. Two studies were carried out to better understand the hydration behaviour: i) an in-situ synchrotron X-ray powder diffraction (SXRPD) study for the first hours of hydration at ALBA synchrotron (Barcelona); and ii) ex-situ studies at later ages of hydration by laboratory X-ray powder diffraction (LXRPD). The in-situ study showed important differences in the hydration process. In non-active-BCSAF-cement, gypsum and ye'elimite dissolves (completely) earlier than in active one, and then, the AFt content was higher (after 1h). Moreover, under our experimental conditions, β-C2S reacts faster than α'H-C2S to yield stratlingite, and this behaviour may well be justified with the formation of high amounts of ettringite at early hours which implies a concomitant large quantity of amorphous aluminium hydroxide. The availability of amorphous-AH3 promotes the precipitation of stratlingite, from belite reaction. Then, the hydration behaviour of C2S is more dependent on the chemical environment than on its polymorphism. At late ages of hydration (>24h), the same behaviour was found: β-belite reacts at a higher pace than α′H-belite. Ye'elimite reaction kinetics showed a small dependence on the amount of added gypsum. Finally, the hydration of C4AF was strongly retarded by increasing the gypsum content in both (active and non-active) cements. In all cases the main crystalline hydrated compounds were ettringite, stratlingite and katoite. The amount of crystallised ettringite in active-cements resulted higher than that in non-active-cements, irrespective of gypsum content. The in-situ SXRPD study of BCSAF cements with different calcium sulphate sources showed that the dissolution kinetic of anhydrite is much slower than that for gypsum or bassanite, and as a consequence the precipitation of ettringite is the lowest. Moreover, the reactivity of ye'elimite with water to form AFm as main hydrated phase has not taken place. At late ages of hydration (>24h), the sulphate source was always consumed before 3 days of hydration to form ettringite (main crystalline hydrated phase), and variable amounts of AFm and stratlingite. Independently of the sulphate source, ettringite seems to be more stable in active cements, as it is almost constant with time of hydration. At latter ages, the analysis of the data indicates that the phase assemblage is slightly sensitive to the initial sulphate source. Since our objective is to study the effect of the calcium sulphate source (including compressive strengths of the corresponding mortars) similar rheological behaviour at very early hydration ages are desired. In this case a small amount of a commercial polycarboxylate-based superplasticizer was added to water to prepare bassanite-containing pastes. They exhibited a considerable diminishing in viscosity and similar rheological behaviour to those prepared with gypsum or anhydrite. Mechanical properties of standard mortars were prepared with a cement/sand/water ratio of 1/3/0.55. The most important result is that all mortars prepared with the active-BCSAF cement developed higher compressive strengths than non-active mortars, independently of the type and amount of sulphate source. Within the non-active mortars, anhydrite-mortar presented the highest value, which may be explained/justified by the higher BET area of the particles and the slightly higher stability of AFt when compared to the gypsum-mortar. For bassanite-mortar, although the addition of a small amount of SP improved the workability, the delay in the setting time was not enough to develop comparable mechanical strength values to other mortars. Within the active-mortars, at 120 days, gypsum-mortar developed the highest mechanical strength value (68±1 MPa), even when the amount of ettringite in other pastes was slightly larger. Therefore, we are forced to conclude that the amorphous contents are playing a key role in the strength development at late ages. Moreover, the active gypsum-cement has the highest BET area value and the pastes shows the lowest porosity values (10%) at that age (120 days); this behaviour also helps to justify the measured mechanical strengths.
Keywords: Cemento - Tesis doctorales; Hydration; X-ray; Sulpho-belite cement; Diffraction; Rietveld method; Mechanical properties